Cyber crime : concepts, methodologies, tools and applications - Information Resources Management Association (Hershey, P.A. : Information Science Reference)
"This is a three-volume reference that explores all aspects of computer-based crime and threats, offering solutions and best practices from experts in software development, information security, and law"--Provided by publisher.